KNOWLEDGE OF RATIONAL USE OF MEDICINE AMONG NURSING STUDENTS - Yusshy Kurnia Herliani; Hasniatisari Harun; Anita Setyawati; Siti Ulfah Rifa'atul Fitri (The Indonesian Journal of Public Health, 2022)
Introduction: Rational use of medicine (RUM) is critical for achieving therapeutic goals and avoiding unwanted effects. However, irrational medicine use is becoming a severe issue worldwide since it leads to increased medical costs and unwanted effects. Students as prospective professional nurses need to have knowledge that supports the rational use of medicine to ensure rational administration of the medicine for patients. Methods: This descriptive research was conducted to identify knowledge of rational use of medicine among nursing students of Faculty of Nursing Universitas Padjadjaran. Quantitative data was collected by asking respondents to fill out questionnaires. A total of 285 respondents had filled out an online research questionnaire (response rate=76.61%). The collected data were analyzed with descriptive analysis (frequency, percentage, and average). Result: The results of this study showed that there is some knowledge related to (RUM) which is not appropriate, such as assuming that over the counter medicines are safe to consume with prescribed medicines (53.3%); tablet medicines can be divided to be administered in child patients (57.9%). In addition, almost all respondents considered it unnecessary to be cautious in giving medication to pregnant and lactating mothers (41.1%) and the elderly (40.4%). Conclusion: Thus, nursing students are expected to gain RUM knowledge to obtain better RUM attitudes and behaviors in providing nursing interventions.